Abundance and vertical distribution of zooplankton in San Pedro Bay Juliet Martinez Aguirre; Margarita T. dela Cruz, adviser. - Aguirre, Juliet Martinez; dela Cruz, Margarita T. (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines in the Visayas Tacloban College, 2009)
Zooplankton plays an important role in our environment, especially to the marine food web. The abundance and distribution of zooplankton is an indicator of the efficiency of the food web in the ocean. This study investigates on the abundance and distribution of zooplankton in San Pedro Bay represented by four (4) different sampling stations. Nauplii belonging to suborder Calanoida and suborder Cyclopoda were observed. In addition, 5 families of the crustacean order Calanoida, 1 family of the crustacean order Amphipoda, 2 families of the foraminiferan order Oligotrichida, and 1 family belonging to the foraminiferan order Globigerinida, The distribution of zooplankton also varied in different depths at different time intervals. It was observed that the copepods or crustacean zooplankton dominates the total composition of zooplankton in the bay. In a significant level of 0.05, it was observed that temperature has a positive correlation with the number of zooplankton in the bay. However, a negative correlation was observed between the number of zooplankton and dissolved oxygen in the four different stations.
Undergraduate thesis (Bachelor of Science in Biology) -- University of the Philippines, Tacloban.